Studying indirect translation : a conversation with and between L. Davier, M. Marin-Lacarta and F. Pochhacker - Davier Lucile; Marin-Lacarta Maialen; Poechhacker Franz; Gambier Yves; Ivaska Laura; Pieta Hanna (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Focused on key issues in researching indirect translation, this article presents a dialogue with and between three scholars from different branches of Translation Studies: news translation, interpreting and literary translation. The aim of this dialogue is to address fundamental questions concerning the history of indirect translation studies, the methodological challenges faced by researchers investigating this practice, and the impact of English as a lingua franca and recent advancements in machine translation on the quality and future of indirect translations. This intra-disciplinary exchange allows us to identify unique perspectives and potential blind spots in approaches to indirect translation within specific branches of Translation Studies. At the same time, the dialogue sheds light on the various overlaps and complementarities between these approaches. We hope that the insights gained from this dialogue will not only deepen our understanding of indirect translation as a field of practice and research but also foster opportunities for future intra-disciplinary collaborations.